Inappropriate pelvic floor muscle activation during forced exhalation and coughing in elderly female inpatients with urinary incontinence. (March 2022) - Talasz, Helena; Kofler, Markus; Mariacher, Romana; Lechleitner, Monika
Abstract: Background: Reduced pelvic floor muscle (PFM) contraction strength is a common condition in elderly female patients with urinary incontinence (UI). However, little data exist to demonstrate the importance of appropriate PFM activation during exhaling and coughing. Objectives: To analyse breathing and coughing patterns in elderly female inpatients with UI, and to assess PFM activation patterns during exhalation and coughing. Design: Retrospective chart data analysis. Patients and methods: Data from 177 elderly female inpatients with UI were analysed to determine voluntary PFM contraction strength, as well as PFM activation and displacement of the pelvic floor (PF) and abdominal wall during forced exhalation and coughing. Clinical data were obtained by means of inspection and digital palpation in the course of a routine clinical UI assessment. Data collected were correlated with age, body mass index and number of childbirths, and categorised by predominant UI symptoms, history of previous hysterectomy and history of PFM training. Results: Independent of voluntary PFM contraction strength, nearly all patients ( n  = 168) demonstrated bulging of the abdominal wall and PF during forced exhalation and coughing instead of contracting the PFMs and consequently lifting the PF, which would be in accordance with physiological breathing synergies. None of the nine women who reflexively contracted the PFM physiologically in accordance with an expiratory breathing pattern complained of symptoms of stress UI alone. Conclusion: A high percentage of elderly females with UI do not activate their PFMs appropriately during forced exhalation and coughing, possibly contributing to or exacerbating UI.